2006 IEEE International Conference on Communications 2006
DOI: 10.1109/icc.2006.254752
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Body Channel Response and Digital Modulation Schemes for Intra-body Communications

Abstract: Intra-body communications is a short range communication solution suitable for Body Area Networks wherein the human body is used as the transmission medium. Currently, some studies have succeeded to transmit and receive simple information. However, intra-body communications could also provide broadband applications such as video streaming which will need high data rates. In this paper, firstly we investigate the propagation characteristics of the human body as a conductor of radio frequency signals. Afterwards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Jordi Agud Ruiz and Shigeru Shimamoto published a paper [9] in 2006 to investigate the transmission characteristics of the human body considering high radio frequency signals. The experiment results of the frequency domain response have shown that the received signal power decreases when the frequency increases, and the power decrease is faster when the distance between TX and RX is larger.…”
Section: Literature Surveymentioning
confidence: 99%
“…Jordi Agud Ruiz and Shigeru Shimamoto published a paper [9] in 2006 to investigate the transmission characteristics of the human body considering high radio frequency signals. The experiment results of the frequency domain response have shown that the received signal power decreases when the frequency increases, and the power decrease is faster when the distance between TX and RX is larger.…”
Section: Literature Surveymentioning
confidence: 99%
“…[14], [6], [29] and [30] are some of the examples from the reviewed literature whose actual human body propagation loss is masked either due to the direct return path provided by earth grounded lab instruments as shown in receiver ground is connected with instrument ground during measurements to avoid floating ground conditions. The earth grounded lab instruments used for measurements therefore improve transmission for battery operated transmitters and receivers due to their indirect coupling with earth ground as shown in Fig.…”
Section: Tx Rxmentioning
confidence: 99%
“…He considers that quasi-electrostatic assumption is valid under 3 MHz and is dominant over radiation field in this range. Ruiz [12,13] determined suitable frequency range between 200 MHz to 600 MHz for capacitive BCC channel using earth grounded signal generator and wireless communication analyzer for 20 cm and 155 cm distances. Cho [14] determined optimum frequency range between 10 MHz to 100 MHz after measuring electric field intensity from 100 kHz to 150 MHz range using battery operated transmitter but earth grounded digital oscilloscope and spectrum analyzer as receiver for 10 cm, 40 cm and 120 cm distances around both arms.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ruiz and Shimamoto [69], the received power could be modelled as a normal distribution. The modulation methods BPSK, QPSK, 8PSK, 16QAM, and MSK provided symbol rates range from 100 ksps to 5 Msps with transmission power of 15 dBm and carrier frequency of 200 MHz [21,65]. Although MSK achieved the best performance [65], it was the most sensible modulation scheme so that the modulation quality decreased as symbol rate increased [21].…”
Section: Static Body Behaviormentioning
confidence: 99%
“…The communication performance of HBC systems was investigated by using simulations [37] and experiments [17,61,64,65]. Also many prototypes [32,41,60] have been developed to achieve different communication performance.…”
Section: Communication Performance Of Hbc Systemsmentioning
confidence: 99%